Obvezni in neobvezni členki - Smolej, Mojca (Slavistična revija, 2004)
Based on syntactic semantic, text-formational, and pragmatic communicative analyses of particles, the article sheds light on this part of speech from the point of view of its obligatoriness and non-obligatoriness in the clause/sentence and the text. When the particle is obligatory, its removal from the sentence impars the communicative form of the sentence, as it becomes incapable to take part functionally in building the illocutionary value that the sentence had before the removal of the particle. The impairment of the communicative form always results in the impairment and disruption of the communicative logical flow. When the particle is optional, it can be removed from the sentence without impairing the communicative form of the sentence or the structure of the text (or the textual logical flow).
Keywords: členek (ling.); Slovene; slovenščina